Home oxygen therapy: evidence versus reality. (3rd June 2017) - Magnet, F. S.; Storre, J. H.; Windisch, W.
ABSTRACT: Introduction : LTOT is a well-established treatment option for hypoxemic patients. Scientific evidence for its benefits of LTOT dates back to the 1980s, when two randomized controlled trials showed prolonged survival in COPD-patients undergoing LTOT for at least 15 hours/day. In contrast, the potential benefits of LTOT in non-COPD-patients has not been well researched and the recommendations for its application are primarily extrapolated from trials on COPD-patients. Recently, a large trial confirmed that COPD-patients who don't meet classic indication criteria, and have moderate desaturation at rest or during exercise, do not benefit from oxygen therapy. Also the significant technical evolution of LTOT devices has improved its application. Areas covered : A literature research was performed in pubmed regarding home oxygen therapy (terms: LTOT, ambulatory oxygen therapy, short burst oxygen therapy, nocturnal oxygen therapy). Expert c ommentary : LTOT proved a survival benefit for COPD patients about 30 years ago. Whether the results of these trials are still valid for patients under modern treatment guidelines remains unknown. Nevertheless, the classic indication criteria for LTOT still persist in guidelines, since there is a lack of updated evidence for the effects of LTOT in more severe hypoxemic patients.